On cubic formulas related to the mixed Hermite splines - Myrzanov, Zh. E. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A cubic formula containing partial integrals is considered on a class of functions of two variables. It is shown that the integral of a mixed Hermite spline gives the best cubic formula for the given class. The coincidence of cubic formulas, which are exact for odd and even mixed Hermite splines, is established.